Eksplorasi Kasus Lingkungan dengan Pendekatan Socio-Scientific Issues pada Pembelajaran Rantai Makanan Berbasis PBL di SD - Majid, Annis Annafik; Hana Rosita; Susantini, Endang; Julianto, Julianto (LPPM Institut Pendidikan Nusantara Global, 2025)
Science learning in elementary schools ideally not only teaches scientific concepts, but also fosters students' awareness of environmental issues relevant to their lives. However, in reality, science learning tends to be theoretical and lacks linking concepts with the social and ecological context around students. For example, the food chain material is often taught simply as a sequence of relationships between living things without discussing the impact of human activities on the balance of the ecosystem. To address this gap, this research aims to explore environmental cases that match the characteristics of Socio-Scientific Issues (SSI) on food chain material in grade V SD and develop a Problem-Based Learning (PBL)-based food chain learning design integrated with the SSI approach systematically based on the environmental cases found. This research uses a qualitative approach with the type of multiple case study. Data collection techniques were conducted through online news documentation from credible mass media relevant to ecosystem and food chain issues. The data were analyzed using the Miles and Huberman model which includes the stages of data condensation, data presentation, and conclusion drawing. The results showed that five environmental cases were found, namely the decline in the frog population, python visits to settlements, locust attacks, caterpillar population explosion, and owl hunting. The five cases fulfill the characteristics of SSI and have high potential to be used as a context for elementary science learning. Based on these findings, a PBL-based learning design was developed that integrates SSI elements to shape conceptual understanding, critical thinking skills, and environmental awareness in elementary school students.